PENGARUH PELATIHAN JUMP SERVICE DENGAN DAN TANPA AWALAN TERHADAP DAYA LEDAK OTOT TUNGKAI - Galih Hari Cahyadi, I Made (Universitas Pendidikan Ganesha, 2013)
This research aimed to determine the effect of jump service training with the prefix and without the prefik of the leg muscle explosive power. This research type is a quasi-experimental research design with nonrandomized control goup the pre-test post-test design. The subjects were men's students volleyball extracurricular participants in SMA Negeri 1 Selemadeg Tabanan school year 2012/2013 as many as 30 people. Explosive leg muscle power is measured by using a vertical jump test. Data were analyzed by Anava with SPSS 16.0 the results variable leg muscle explosive power to jump service training group with and without the prefix with a significance of 0.000, significance is smaller than α (Sig <0.05), so the research hypothesis